2019
DOI: 10.1371/journal.pone.0214065
|View full text |Cite
|
Sign up to set email alerts
|

Decreased orbital fat and enophthalmos due to bimatoprost: Quantitative analysis using magnetic resonance imaging

Abstract: We quantitatively determined the relation between the decrease in orbital fat and enophthalmos due to bimatoprost using magnetic resonance imaging (MRI). Nine orbits in nine patients were treated unilaterally with bimatoprost for glaucoma or ocular hypertension. The contralateral orbits were used as controls. The volumes of the orbital tissues and the enophthalmos were measured using MRI. The mean volumes on the treated and untreated sides were, respectively, 14.6 ± 2.1 and 17.0 ± 4.3 cm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…11,45,46 One retrospective study has suggested that enophthalmos may occur in eyes unilaterally treated with latanoprost. 47 However, enophthalmos is not typically reported in patients with POAG and would not have been significant in the small unilateral treatment study by Higashiyama et al, 12 except with the inclusion of one marked outlier case.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…11,45,46 One retrospective study has suggested that enophthalmos may occur in eyes unilaterally treated with latanoprost. 47 However, enophthalmos is not typically reported in patients with POAG and would not have been significant in the small unilateral treatment study by Higashiyama et al, 12 except with the inclusion of one marked outlier case.…”
Section: Discussionmentioning
confidence: 98%
“…However, since Asian subjects with and without POAG had smaller OV than non-Asians, the possibility of a relationship between orbital size and POAG at normal IOP warrants further investigation. The Higashiyama et al 12 study used MRI to compare OFV in nine patients treated monocularly with brimatoprost for secondary glaucomas for at least 11 months. These authors reported mean OFV to be significantly smaller in the treated than nontreated eye.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations